(untitled) (Journal of Informatics Education and Research, 2024)
In terms of highest population, India lately passed China and took first spot. In its study, Reserve Bank of India reaffirmed that India will stay at fifth place among economies in 2023. It also claimed that India’s GDP in 2023 will reach USD 3.7 trillion. However, it is also evident that the proportion of agriculture in Indian GDP has dropped across time. The Ministry of Statistics & Program Implementation (MoSPI) projects that the Gross Value Added (GVA) of agriculture and associated sectors in 2020–21 was 20.1%; in 2021–22 it was 19%; and in 2022–23 it once more dropped to 18.3%. The issues India would have to satisfy the food demand from its growing population are easily understandable. Moreover, a poor agricultural exhibition might affect the general state of affairs in agriculture all around. Indian government is acting in several ways to revive the agricultural sector. One such action is institutional financing accessible for the allied industry including agriculture. This research looks at the function institutional credit serves in the agricultural industry. Analyzed are time series data on the institutional credit and other criteria.